2000
DOI: 10.1074/jbc.m004681200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of 1-Aminocyclopropane-1-carboxylate Deaminase from Hansenula saturnus

Abstract: The pyridoxal 5-phosphate (PLP)-dependent enzyme 1-aminocyclopropane-1-carboxylate deaminase (ACCD) catalyzes a reaction that involves a ring opening of cyclopropanoid amino acid, yielding ␣-ketobutyrate and ammonia. Unlike other PLP-dependent enzymes, this enzyme has no ␣-hydrogen atom in the substrate. Thus, a unique mechanism for the bond cleavage is expected. The crystal structure of ACCD from Hansenula saturnus has been determined at 2.0 Å resolution by the multiple wavelength anomalous diffraction method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 40 publications
1
85
0
Order By: Relevance
“…AtOASS, the bacterial OASS, and other enzymes requiring PLP as a cofactor share a common topology in the PLP-and substrate-binding domains (24,(32)(33)(34)(35)(36)(37). The overall ␣/␤-domain structure maintains the PLP binding site with sequence variations in the active site diversifying substrate recognition and reaction chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AtOASS, the bacterial OASS, and other enzymes requiring PLP as a cofactor share a common topology in the PLP-and substrate-binding domains (24,(32)(33)(34)(35)(36)(37). The overall ␣/␤-domain structure maintains the PLP binding site with sequence variations in the active site diversifying substrate recognition and reaction chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…A search of the Protein Data Bank using DALI (31) showed that AtOASS shares a similar three-dimensional fold with E. coli threonine deaminase (32), S. typhimurium tryptophan synthase ␤-subunit (33), Sacchromyces cerevisiae threonine synthase (34), Arabidopsis threonine synthase (35), Rattus norvegicus serine dehydratase (36), and Hansenula saturnus 1-aminocyclopropane-1-carboxylate deaminase (37). AtOASS is related by 14 -21% amino acid sequence identity to these proteins with r.m.s.…”
Section: Three-dimensional Structurementioning
confidence: 99%
“…ACP (26% identity, 40% similarity), Penicillium citrinum (26% identity, 39% similarity), and Hansenula saturnus (22% identity, 36% similarity) (26 -29). The similarity between NocJ and the ACC deaminases is not particularly strong, but careful analysis of the alignments with these proteins, however, revealed the greatest similarity was observed in the immediate vicinity of the lysine residue responsible for binding the PLP cofactor (30,31). Examination of the region surrounding the PLP-binding lysine revealed NocJ also contains a lysine at this position, corresponding to Lys 51 of the H. saturnus enzyme.…”
Section: Analysis Of Nocj-mentioning
confidence: 99%
“…By analogy to the other enzymes, those extensions could be involved in regulation too. Very recently, Yao et al (2000) published the structure of aminocyclopropane carboxylate deaminase, which has a similar fold to domains 2 and 3 of TS and is not allosteric.…”
Section: Structure Comparison With Three Plp Enzymes Of the Second Fomentioning
confidence: 99%